Productive rigidity: why electronic document and records management systems still matter in Estonia’s public sector - Sidra Azmat Butt; Ingrid Pappel; Dirk Draheim; Riina Palu (Records Management Journal, 2026)
Purpose This study aims to examine why electronic document and records management systems (EDRMS) continue to play a central role in digitally advanced public-sector environments, despite the rise of cloud collaboration and artificial intelligence (AI) tools, using Estonia as a case. The paper introduces productive rigidity to explain how compliance structures stabilise recordkeeping while still allowing gradual change. Design/methodology/approach A qualitative case study approach: five semi-structured interviews with senior officials and specialists from central government ministries and the State Shared Service Centre, selected through purposive sampling for their EDRMS or records management responsibility, complemented by documentary analysis. Data were analysed using a hybrid inductive and deductive thematic analysis. Findings EDRMS in Estonia function as institutional infrastructures anchored in legal mandates, organisational routines and national digital architectures. Compliance sustains their central role, while usability challenges, metadata burdens, organisational variability and a large share of information held outside the EDRMS in line-of-business systems persist. AI is viewed as a future opportunity, dependent on improved data quality and governance. Social implications By supporting accountability and trustworthy digital records, well-governed EDRMS contribute to public trust in digital government. Originality/value The study introduces productive rigidity to explain how legal, technical and organisational constraints stabilise recordkeeping while enabling controlled transformation, connecting recordkeeping-culture and AI-in-archives literatures, which have received limited attention in government recordkeeping, to an empirical public-sector setting.